Andragogical Multidimensional Ethnography - Borowska-Beszta, Beata (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The following chapter is structured based on analyses of three contexts of andragogicalethnography. First, it is a synthesis of the justifications for implementing ethnographyin andragogy. Second, it contains a methodological description of the multifacetedpossibilities of conducting ethnographic research. Third, it contains a descriptionof the researcher’s learning during and after the implementation of selected eight ethnographicresearch projects of different scope and range, Polish and foreign.